An unusual complex karyotype in myopericytoma - James, Aaron W. (J Orthop, 2015)
INTRODUCTION: Myopericytoma is a perivascular neoplasm commonly found in the skin and soft tissue of extremities. These lesions often exhibit concentric vascular proliferation of spindle shaped myoid cells. METHODS/RESULTS: We present a case of a 76-year old male who was diagnosed with myopericytoma and subsequent cytogenetic analysis found a highly abnormal karyotype. This karyotype includes cytogenetic mutations that have not been described in previous case studies of myopericytoma. CONCLUSIONS: Some of these aberrations occur on genes that are involved in hedgehog signaling as well as pericyte proliferation, indicating a potential pericyte origin for myopericytoma tumors.